Technology Capability and the Internationalization Strategies of New Ventures - Zou, Huan; Liu, Xiaohui; Ghauri, Pervez (Organizations and Markets in Emerging Economies, 2010)
This study investigates the impact of technological capability and the combination of technological capability, networking capability and financial capital on growth strategies adopted by new ventures in China. Technological capability needs leveraging through the process of combining with other capabilities. The results show that the interaction between technological capability and networking capability increases the possibility that a new venture chooses an internationalisation strategy. Technology capability provides a base to allow networks to have a positive impact on internationalisation strategies. The findings from the study provide a better understanding of technology capability and its impact on internationalisation strategies. This study also generates some important implications for high-tech new ventures in emerging economies.